Tracking Coronavirus 2019 pandemic-related waste generation in urban waterways - R.G. Banal; I.L.M. Abad (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The Coronavirus 2019 pandemic has revealed significant shortcomings in the Philippines’ solid waste management system, particularly in addressing the surge of pandemic-related waste. Unreliable waste collection, insufficient public knowledge, and improper waste disposal practices have exacerbated risks to the environment and public health. Despite these concerns, the specific impacts of Coronavirus 2019 pandemic related waste on human health and the environment in the Philippines’ context remain underexplored. This study aims to quantify Coronavirus 2019 related waste generated from both household sources and non-household establishments, assess disposal practices, characterize waste composition, determine generation rates, and classify waste types. Moreover, a comprehensive waste flow analysis will be carried out to monitor the movement of both appropriately and inappropriately managed Coronavirus 2019 waste, examining its implications on terrestrial and aquatic environments, as well as public health. Insights from the Philippines can significantly contribute to the formulation of resilient and adaptive waste management approaches in response to future public health emergencies worldwide.METHODS: Coronavirus 2019 pandemic related waste generation from both household sources and non-household establishments was quantified through a 5-day at-source waste analysis and characterization study conducted in twenty-six urban and rural barangays of General Santos City. The determination of sample sizes was conducted using conventional statistical techniques, informed by the most up-to-date census data and business establishment profiles. Structured questionnaires and checklists were used to gather information from household respondents regarding Coronavirus 2019 related waste sources, generation rates, and disposal behaviors. To determine the degree of environmental contamination related to pandemic waste, further waste characterization was carried out in the Silway and Makar Rivers, two key urban waterways that pass through populated and commercial districts prior to their discharge into Sarangani Bay.FINDINGS: According to the Waste Analysis and Characterization Study, waste linked to the Coronavirus 2019 pandemic totals about 52,877.7 kilograms per day, which is equivalent to 1.57 percent of the city’s total daily waste. This equates to an estimated 4,654,720 discarded face masks from household sources and 633,050 from non-household establishments daily. Coronavirus 2019 pandemic related waste density in the Makar and Silway Rivers-tributaries of the Sarangani Bay Protected Seascape was recorded at 0.238 gram per square meters and 0.706 gram per square meters, respectively. Mainly consisting of plastic face masks, this waste poses environmental threats as possible microplastic sources, jeopardizing both marine environments and human well-being. Waste flow analysis illustrated the management pathways of Coronavirus 2019 pandemic-related waste, underscoring its significant environmental and social repercussions.CONCLUSION: The Coronavirus 2019 pandemic has highlighted critical gaps in waste management systems and the environmental and health hazards associated with emerging waste streams such as Coronavirus 2019. Mismanagement of this waste stream results in environmental damage and considerable threats to public health. The study emphasizes the pressing requirement for better waste governance, infrastructure enhancements, and public education to reduce the enduring effects of waste associated with the pandemic.